A Comparison of Internationalization Indicators of Evaluation for Higher Education among the Three Quality Assurance Agencies in Taiwan - Wang , Yang-Chih; Wang, Ru-Jer (Advances in Social Sciences Research Journal, 2023)
In line with the internationalization of higher education, the quality assurance and evaluation of higher education is a global phenomenon. It is critical to examine whether internationalization is considered one of the crucial indicators in evaluating higher education. The research aims to examine the internationalization indicators and compare them in the three Quality Assurance Agencies in Taiwan. The methods of documentary analysis and comparative analysis were employed in the study. Based on the results, it can be concluded: in terms of internationalization as an indicator for higher education evaluation, of the three QA agencies in Taiwan, the TWAEA and the IEET take it into account; in contrast, the HEEACT has it as part of its purposes. Because international competence is essential in a globalized employment market, the university is responsible for internationalizing its students. Although a diversity of evaluation indicators is expected in Taiwan, some indicators are considered universal, including internationalization.